Sistem Pakar Pemilihan Menu Diet Sesuai Kondisi Kesehatan Pasien - Kusumadewi, Ni Putu Ari; Permana, Agus Aan Jiwa; Swari, Gusti Putu Ayu Mas Meita Pradnya; Yudhantara, Kadek Prasta; Mahagangga, Komang Adi Satya; Artha, I Komang Windra (Lembaga Yasin AlSys, 2025)
Expert Systems, a branch of artificial intelligence, are designed to replicate decision-making capabilities of human experts. This study focuses on developing an Expert System for Diet Menu Selection Based on Health Conditions. The system aims to assist users in planning nutritious and balanced diets tailored to individual health profiles, thereby enhancing health management through clear and practical guidelines. The Forward Chaining inference method is employed to derive conclusions from known health data, while the Agile development methodology supports iterative progress, adaptability to changes, and active stakeholder involvement to ensure optimal functionality. Given the rising public awareness of healthy living, this system presents a practical and innovative alternative for individuals seeking to manage their dietary habits effectively—without the need for constant consultations with nutritionists.